EPS SEBAGAI VARIABEL INTERVENING ANTARA PROFITABILITAS, SOLVABILITAS, DAN LIKUIDITAS TERHADAP HARGA SAHAM - Fadillah Citra Ardhana; Saiful Anwar (Jambura Economic Education Journal, 2023)
This study aims to find the effect of profitability, solvency, and liquidity on stock prices through earnings per share. The population is 787 companies on the IDX until 2021 and purposive sampling is the sample shopping technique, resulting in 30 LQ45 index companies during the 2019-2021 period. Partial Least Square (PLS) is the data analysis technique and then obtains the result that partially it is found that there is an influence that has a positive direction but is not significant by profitability, solvency, and liquidity on stock prices, while only EPS has an effect on stock prices with a significant positive direction. If partially on EPS, there is a negative effect that is not significant by profitability and liquidity, while by solvency there is a negative effect which is significant. As well as partially on stock prices through EPS, there is a negative effect that is not significant for profitability and liquidity, while for solvency there is a significant negative effect.